Paste for electronic components
Patent Information
- Application Number
- JP2023564783
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-01
- Filing Date
- 2022-10-15
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2042-10-15
Smart Images

Figure 0007652287000009 
Figure 0007652287000010 
Figure 0007652287000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a paste for electronic components, which is used in the production of electronic components and contains inorganic particles, a dispersant, a binder, and an organic solvent, and in particular to an improvement in the binder. [Background technology]
[0002] For example, JP 2018-168238 A (Patent Document 1) describes a paste for electronic components, i.e., a conductive paste, which is useful for forming internal electrodes in a multilayer ceramic capacitor as an electronic component. This conductive paste contains a conductive powder, an organic resin (hereinafter referred to as "binder"), an organic solvent, an additive, and a dielectric powder, and the binder is composed of only ethyl cellulose, the organic solvent is composed of only terpineol, and the additive is composed of a composition containing an unsaturated carboxylic acid-based dispersant and an oleylamine-based dispersant. Patent Document 1 exemplifies nickel powder as the conductive powder and ceramic powder as the dielectric powder.
[0003] In addition, in this conductive paste, the content of the unsaturated carboxylic acid-based dispersant in the additive is 0.2 mass% or more and 1.2 mass% or less with respect to the total amount of the conductive paste, and the content of the oleylamine-based dispersant in the additive is 0.3 mass% or more and 2.0 mass% or less with respect to the total amount of the conductive paste. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-168238 A Summary of the Invention [Problem to be solved by the invention]
[0005] It is generally known that cellulose has a hydroxyl group at one non-reducing end and a tautomer of a hydroxyl group and a formyl group at the other reducing end. With regard to the above-mentioned ethyl cellulose as a binder, it can be easily assumed that most of the terminal hydroxyl groups are converted to ethoxy groups due to the known manufacturing process. Therefore, it can be said that one end of normal ethyl cellulose (corresponding to the non-reducing end of cellulose) is an ethoxy group, and the other end (corresponding to the reducing end of cellulose) is an ethoxy group or a formyl group.
[0006] General dispersants have alkyl, ether or ester chains, so they have weak adhesive strength with ethyl cellulose. In addition, in the conductive paste, not all of the ethyl cellulose used as a binder is adsorbed to inorganic particles such as nickel particles and ceramic particles, and some of it is not adsorbed to any of the inorganic particles.
[0007] Therefore, the adhesive strength at the interface between the dispersant adsorbed on the surface of the inorganic particles and the ethyl cellulose not adsorbed thereon is weakened, and as a result, the adhesive strength between the inorganic particles in the conductive paste, more specifically, between the nickel particles, between the ceramic particles, or between the nickel particles and the ceramic particles is weakened. This tends to cause cohesive failure (peeling within the internal electrode layer) between the nickel particles, between the ceramic particles, or between the nickel particles and the ceramic particles in the internal electrodes during the manufacturing process of the multilayer ceramic capacitor. Cohesive failure in the internal electrodes causes peeling within the internal electrode layer when the laminate is pressed and cut before firing, delamination of the multilayer ceramic capacitor after firing, and a decrease in the moisture resistance of the multilayer ceramic capacitor after baking the external electrodes, so it is necessary to prevent it as much as possible.
[0008] One method to improve the interparticle adhesion is to increase the amount of ethyl cellulose, which is a binder, but increasing the amount of binder reduces the filling rate of nickel particles in the internal electrode coating, resulting in a decrease in internal electrode coverage after firing.
[0009] On the other hand, if the conductive paste does not contain a dispersant, the interface with weak adhesive strength can be eliminated, but it is difficult to ensure the dispersibility of the conductive paste without a dispersant.
[0010] Therefore, it is necessary to improve the adhesive strength between inorganic particles such as nickel particles and ceramic particles without increasing the amount of binder while still containing a dispersant.
[0011] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a paste for electronic components that can satisfy the above-mentioned demands. [Means for solving the problem]
[0012] The present invention is directed to a paste for electronic components, which contains inorganic particles, a dispersant, a binder, and an organic solvent, and is characterized in that the binder includes a first binder adsorbed to the surfaces of the inorganic particles and a second binder not adsorbed to the surfaces of the inorganic particles, and at least the first binder is a cellulose derivative having a carboxyl group or a carboxylate salt at one end. Effect of the Invention
[0013] According to the paste for electronic components of the present invention, even if the adhesive strength at the interface between the dispersant adsorbed on the surface of the inorganic particles and the second binder not adsorbed on the inorganic particles is low, the adhesive strength at the interface between the cellulose derivative having a carboxyl group at one end or a carboxylate at one end as the first binder adsorbed on the surface of the inorganic particles and the second binder not adsorbed on the surface of the inorganic particles is high. As a result, the adhesive strength between the inorganic particles is improved in total through the high adhesive strength at the interface between the first binder and the second binder. Therefore, when the present invention is applied to a conductive paste for internal electrodes used in the manufacture of a multilayer ceramic capacitor, for example, it is possible to make it difficult for cohesive failure (peeling within the internal electrode layer) to occur between metal particles, between ceramic particles, or between metal particles and ceramic particles. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a diagram for explaining the effect of the paste for electronic components according to the present invention, and is a schematic diagram showing, in a case where a comb-type polymer dispersant 2 is contained, (A) a state in which only the dispersant 2 is adsorbed onto the inorganic particle 1, and (B) a state in which the dispersant 2 and a first binder 5 are adsorbed onto the inorganic particle 1. [Diagram 2] FIG. 1 is a diagram for explaining the effect of the paste for electronic components according to the present invention, and is a schematic diagram showing, in a case where a low molecular weight dispersant 3 is contained, (A) a state in which only the dispersant 3 is adsorbed onto the inorganic particle 1, and (B) a state in which the dispersant 3 and a first binder 5 are adsorbed onto the inorganic particle 1. [Diagram 3] FIG. 1 shows a 1H-NMR spectrum of an ethyl cellulose derivative. [Figure 4] FIG. 1 shows the correlation between the molecular weight of ethyl cellulose determined by NMR and that determined by GPC. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The paste for electronic components according to the present invention includes inorganic particles, a dispersant, a binder, and an organic solvent. The binder includes a first binder adsorbed to the surfaces of the inorganic particles, and a second binder not adsorbed to the surfaces of the inorganic particles. At least the first binder is a cellulose derivative having a carboxyl group at one end or a carboxylate at one end.
[0016] Here, it is noted that the cellulose derivative having a carboxyl group or a carboxylate at one end as the first binder has a size of several tens to several hundreds of nm, which is longer than the steric repulsion part of the dispersant (the side chain in the case of a comb-type dispersant, and the main chain in the case of a one-end adsorption dispersant). The polystyrene-equivalent molecular weight Mn of cellulose derivatives generally available on the market is about 10,000 to 90,000, and the size is about 25 to 225 nm.
[0017] At the paste stage, dispersants generally adsorb to the particle surface and form a layer of molecular chains several nanometers long (corresponding to the length of the side chain in the case of polymeric dispersants and the length of the main chain in the case of low molecular dispersants), thereby achieving dispersion stabilization through wetting with the solvent and steric repulsion. However, at the dry film stage, there is a problem of low adhesive strength due to poor compatibility at the interface between the binder and the steric repulsive parts of the dispersant several nanometers long (side chains in the case of comb-type dispersants and main chains in the case of one-end adsorbed dispersants). It is speculated that this is because the dispersant arranges molecular chains at narrow intervals on the particle surface to form steric repulsive parts, making it difficult for adhesive strength to be expressed between the binder and the molecular chains of the dispersant due to steric constraints.
[0018] The above-mentioned state will be described with reference to Figures 1 and 2. In Figure 1(A), a comb-shaped polymer dispersant (hereinafter referred to as "polymer dispersant") 2 is adsorbed to the surface of an inorganic particle 1. In Figure 2(A), a low molecular weight dispersant adsorbed at one end (hereinafter referred to as "low molecular weight dispersant") 3 is adsorbed to the surface of an inorganic particle 1. The polymer dispersant 2 and the low molecular weight dispersant 3 form steric repulsion parts by arranging molecular chains at narrow intervals on the surface of the inorganic particle 1, so that for a second binder 4 made of a cellulose derivative, for example, the binder is unlikely to exhibit adhesive strength between the molecular chains of the dispersant 2 or 3 (poor compatibility).
[0019] Here, as shown in Figures 1(B) and 2(B), if a cellulose derivative having a carboxyl group or a carboxylate salt at one end, which is several tens to several hundreds of nm in size and longer than the steric repulsion portion of the dispersant 2 or 3 (the side chain in the case of the comb-type polymer dispersant 2, or the main chain in the case of a dispersant such as the low molecular weight dispersant 3 that is adsorbed at one end, is used as the first binder 5 in the gaps on the surface of the inorganic particle 1 where the dispersant 2 or 3 is not adsorbed, the molecular chains will be arranged at wide intervals, making it difficult for steric constraints to arise, and it is thought that the second binder 4 and the first binder 5 will be oriented and adhesive strength will be easily expressed.
[0020] As a result, the contact between the first binder 5 and the second binder 4 increases, and the adhesive force between the inorganic particles 1 can be improved.
[0021] In this invention, the binder adsorbed on the surface of the inorganic particles is defined as the "first binder", and the binder not adsorbed on the surface of the inorganic particles is defined as the "second binder". Therefore, the second binder may be a binder having the same composition as the first binder, that is, both of them may be cellulose derivatives having a carboxyl group or a carboxylate at one end. Of course, the second binder may be a cellulose derivative that does not have a carboxyl group or a carboxylate at one end.
[0022] It is particularly preferable that the second binder is a copolymer having a cellulose derivative portion (any terminal may be used) or a mixture of multiple polymers including a cellulose derivative. In this form, a strong intermolecular force acts between the cellulose derivative adsorbed at one terminal in the first binder on the surface of the inorganic particles and the cellulose derivative portion of the second binder, resulting in a high adhesive strength improvement effect.
[0023] The inorganic particle surface adsorption rate of cellulose derivatives with a carboxyl group or carboxylate at one end is not 100%. This is because it is a single-point adsorption, and the adsorption phenomenon is not completely irreversible. The inorganic particle surface adsorption rate varies depending on the chemical state and surface area of the inorganic particle surface, the type of solvent contained in the paste for electronic components, and the amount and concentration of binder added in the paste for electronic components. In areas where the amount is not excessive, about 30 to 90% of the amount added is adsorbed.
[0024] In summary, when the binder does not contain a cellulose derivative having a carboxyl group at one end or a carboxylate salt at one end, the interface that predominates is one having low adhesive strength between a dispersant 2 or 3 adsorbed on the surface of an inorganic particle 1 and a second binder 4, for example a cellulose derivative, that is not adsorbed on the inorganic particle 1, as shown in Figures 1(A) and 2(A).
[0025] In contrast, when the binder contains a first binder 5 made of a cellulose derivative having a carboxyl group at one end or a carboxylate at one end, as shown in Figures 1(B) and 2(B), not only is there an interface having only low adhesive strength between the dispersant 2 or 3 adsorbed on the surface of the inorganic particle 1 and the second binder 4 not adsorbed on the surface of the inorganic particle 1 and made of, for example, a cellulose derivative, but there is also an interface having high adhesive strength between the first binder 5 adsorbed on the surface of the inorganic particle 1 and made of a cellulose derivative having a carboxyl group at one end or a carboxylate at one end, and the second binder 4 not adsorbed on the surface of the inorganic particle 1 and made of, for example, a cellulose derivative, as shown in Figures 1(B) and 2(B). As a result, the adhesive strength between the inorganic particles 1 is improved overall.
[0026] More specifically, cohesive failure is less likely to occur between metal particles, between ceramic particles, or between metal particles and ceramic particles. When this paste for electronic components is applied to a conductive paste for internal electrodes used, for example, in the manufacture of multilayer ceramic capacitors, peeling of the internal electrode layer can be made less likely to occur, particularly when the laminate is press-cut before being fired.
[0027] In the paste for electronic components, the cellulose derivative having a carboxyl group at one end or a carboxylate at one end as the first binder is 1.0 mg / m2 relative to the total surface area of the inorganic particles. 2 ~5.0mg / m 2 In other words, the cellulose derivative having a carboxyl group at one end or a carboxylate at one end as the first binder is preferably contained in an amount of 1.0 mg / m2 relative to the total surface area of the inorganic particles. 2 ~5.0mg / m 2 It is preferable that the amount of adsorption is 1.0 mg / m 2 This is because a significant effect appears when the concentration is 5.0 mg / m 2 It is unlikely that adsorption will exceed this amount.
[0028] The cellulose derivative having a one-terminal carboxyl group or one-terminal carboxylate is preferably a cellulose ether having a one-terminal carboxyl group or one-terminal carboxylate, because, in consideration of the synthesis reaction scheme described later, it is more practical to obtain a cellulose ether having a one-terminal carboxyl group or one-terminal carboxylate as the cellulose derivative having a one-terminal carboxyl group or one-terminal carboxylate.
[0029] The cellulose ether having a carboxyl group at one end or a carboxylate group at one end is more preferably at least one selected from methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, ethylhydroxyethyl cellulose and hydroxypropylmethyl cellulose.
[0030] As described above, the dispersant contained in the paste for electronic components is preferably a comb-shaped polymer dispersant or a low molecular weight one-end adsorption dispersant. As the comb-shaped polymer dispersant, for example, a polycarboxylic acid dispersant is used. Comb-shaped polymer dispersants such as polycarboxylic acid dispersants and low molecular weight one-end adsorption dispersants form steric repulsion parts by arranging molecular chains at narrow intervals on the surface of inorganic particles, so there is a problem that the adhesive force between the binder and the dispersant molecular chains is difficult to express (poor compatibility) due to steric constraints. However, this problem is advantageously solved by the cellulose derivative having a one-end carboxyl group or one-end carboxylate salt as the binder contained in the paste for electronic components according to the present invention, as described above.
[0031] The inorganic particles contained in the paste for electronic components according to the present invention preferably include at least one of ceramic particles and metal particles. For example, a paste for forming a dielectric layer in a multilayer ceramic capacitor includes at least ceramic particles, and a paste for forming an internal electrode layer includes at least metal particles. The ceramic particles include at least one element selected from Ba, Ti, Ca, Zr, and Sr, for example. The metal particles include at least one metal selected from Cu, Ni, Au, and Ag, for example.
[0032] Experimental Example 1 [Synthesis of cellulose derivatives] In this experimental example, in order to clarify the one-terminal carboxylated cellulose derivative and the one-terminal esterified cellulose derivative to be the binder contained in the paste for electronic components, the synthesis methods for each are shown below. The synthesis methods shown below are synthesis methods using ethyl cellulose, which is a type of cellulose derivative and is widely used in pastes for electronic components. Note that these synthesis methods are merely examples and are not limited to these.
[0033] <Method for synthesizing one-terminal carboxylated cellulose derivative> (1) Oxidation of the reducing end of cellulose to produce cellulose with one carboxylated end A 50% aqueous solution of sodium hydroxide (1680g) was added to a water-dispersed slurry of cellulose (solid content 1440g). After that, sodium anthraquinone-2-sulfonate (24g) dissolved in 30% hydrogen peroxide was added and stirred to oxidize the reducing end of the cellulose, and then filtration and washing with water were performed to obtain cellulose with one end carboxylated. This reaction is a reaction in which the formyl group, which is in a ring-opened state and has a formyl group among the tautomers of the reducing end of cellulose, is oxidized to a carboxyl group.
[0034] Various methods are known for the oxidation reaction of the reducing end of cellulose or the formyl group of ring-opened sugar.
[0035] (2) Deprotonation reaction with sodium hydroxide A 50% aqueous solution of sodium hydroxide was added to an aqueous solution of cellulose with one end carboxylated, and the mixture was stirred at 60°C for 20 minutes to obtain alkali cellulose in which the hydroxyl group was -ONa and one end was -COONa.
[0036] (3) Ethoxylation (etherification) reaction and ethyl esterification reaction with ethyl chloride Alkaline cellulose and ethyl chloride were stirred in a 0.5 MPa pressure cooker at 110°C for 12 hours to obtain ethyl cellulose in which the hydroxyl group was -OEt and one end was -COONa, -COOH, or -COOEt. The amount of sodium hydroxide and the amount of ethyl chloride added were adjusted so that the degree of ethoxylation (DS) for the three OH groups of the monomer unit of the cellulose obtained at this time was in the range of 2.46 to 2.58 (ethoxylation degree 48.0 to 49.5 mass%). In this synthesis, the etherification reaction proceeds more than the esterification reaction, so there is little esterification to -COOEt.
[0037] (4) Hydrolysis of esters The reaction of ethyl cellulose with one end being -COOEt was carried out by hydrolysis to convert the -COOEt to -COOH, obtaining ethyl cellulose with a hydroxyl group of -OEt (degree of substitution 2.5) and one end being -COONa (carboxylate) or -COOH (carboxyl group).
[0038] There are various conditions for hydrolysis, but the reaction can also proceed by adding water to an alcohol solvent and heating. To make the reaction more efficient, it is also a good idea to add a catalyst. Note that since esterification does not proceed easily during the etherification reaction using ethyl chloride, it is possible to obtain ethyl cellulose with most of the ethyl cellulose at one end being -COONa (carboxylate) or -COOH (carboxyl group) even without carrying out this step.
[0039] (5) Washing and drying After removing salts and by-products by washing with hot water, the solid was dried under reduced pressure to obtain a solid ethyl cellulose with an ethoxylation degree of 2.5, in which one end was -COONa (carboxylate) or -COOH (carboxyl group) and the other end was -OEt (ether). By adjusting the number average molecular weight of the cellulose used initially to within the range of 10,000 to 100,000, the number average molecular weight was increased to 1.3 x 10 4 , 2.0×10 4 , 5.4×10 4 , and 8.8 × 10 4 The number average molecular weight was calculated using polystyrene equivalents by GPC (gel permeation chromatography) in THF (tetrahydrofuran) solvent.
[0040] <Method for synthesizing one-terminal esterified cellulose derivative> (1) Oxidation of the reducing end of cellulose to produce cellulose with one carboxylated end As in the synthesis of the one-terminal carboxylated cellulose derivative described above, 50% sodium hydroxide aqueous solution (1680 g) was added to the aqueous dispersion slurry of cellulose (solid content 1440 g). Then, sodium anthraquinone-2-sulfonate (24 g) dissolved in 30% hydrogen peroxide was added and stirred to oxidize the reducing end of the cellulose, followed by filtration and washing with water to obtain one-terminal carboxylated cellulose.
[0041] (2) Deprotonation reaction with sodium hydroxide As in the synthesis of the one-end carboxylated cellulose derivative described above, a 50% aqueous solution of sodium hydroxide was added to the aqueous solution of one-end carboxylated cellulose and stirred at 60°C for 20 minutes to obtain alkali cellulose in which the hydroxyl group was -ONa and one end was -COONa.
[0042] (3) Ethoxylation (etherification) reaction and ethyl esterification reaction with ethyl chloride As in the synthesis of the one-terminal carboxylated cellulose derivative described above, alkali cellulose and ethyl chloride were stirred in a 0.5 MPa pressure cooker at 110°C for 12 hours to obtain ethyl cellulose in which the hydroxyl group was -OEt and one terminal was -COONa, -COOH, or -COOEt. The amounts of sodium hydroxide and ethyl chloride added were adjusted so that the degree of ethoxylation (DS) for the OH group of the cellulose obtained at this time was in the range of 2.46 to 2.58 (ethoxylation degree 48.0 to 49.5% by mass).
[0043] Next, salts and by-products were removed by washing with hot water, and then the mixture was dried under reduced pressure to obtain a solid ethyl cellulose.
[0044] (4) Esterification reaction The solid ethyl cellulose obtained in (3) above was dissolved in ethanol, and concentrated sulfuric acid was added dropwise as an acid catalyst to convert the carboxyl group at one end into an ethyl ester.
[0045] (5) Washing and drying After removing salts and by-products by washing with hot water, the solid was dried under reduced pressure to obtain a solid ethyl cellulose with an ethoxylation degree of 2.5, in which one end was -COOEt (ethyl ester group) and the other end was -OEt (ether). By adjusting the number average molecular weight of the cellulose used initially in the range of 10,000 to 100,000, the number average molecular weight Mn was increased to 1.4 x 10 4 , 2.0×10 4 , 5.2×10 4 , and 8.9 × 10 4 As in the previous case, the number average molecular weight was calculated using GPC in THF solvent in terms of polystyrene.
[0046] <Quantitative analysis of carboxyl groups in one-terminated ethyl cellulose> The amount of carboxyl groups in the one-terminated ethyl cellulose synthesized as described above was 1Quantification was performed using H-NMR measurement. Since it was expected that normal NMR measurement would lack the sensitivity to quantify the small amount of terminal carboxyl groups, a trimethylsilyl (TMS) derivatization method was used.
[0047] The TMS derivatization method is a method of replacing the hydrogen of the hydroxyl group contained in the carboxyl group of ethyl cellulose with a trimethylsilyl group (Si(CH3)3). This derivatization changes the number of hydrogen atoms in the carboxyl group from 1H to 9H, so 1 The detection sensitivity of H-NMR is increased by 9 times.
[0048] The derivatized product is obtained by adding ethyl cellulose and the derivatization reagent (BSTFA) to dehydrated chloroform solvent and heating at 70°C for 1 hour. Since the derivatization reagent acts on both the hydroxyl and carboxyl groups of ethyl cellulose, the amount of the reagent added is approximately 1.5 times the molar amount of the hydroxyl and terminal carboxyl groups of ethyl cellulose. It was confirmed that the quantitative values of the TMS-converted hydroxyl and carboxyl groups do not change even when the amount of the reagent added exceeds 1.5 times the molar amount. The solution after the reaction is returned to room temperature and vacuum dried, and then GPC fractionation is performed to remove the solvent and unreacted derivatization reagent, obtaining a dried product of the derivatized product. This dried product is redissolved in deuterated chloroform, the solvent for NMR measurement, and 1 H-NMR measurement was carried out. 1 The H-NMR spectrum is shown in Figure 3.
[0049] Ethyl cellulose derivatives 1 In the H-NMR spectrum, a peak due to derivatization of the carboxyl group is detected at 0.3 ppm, as indicated by the arrow in Figure 3. 1 The concentration of carboxyl groups in ethyl cellulose was determined by calculating the molar ratio of each from the peak area ratio of the cellulose skeleton, ethoxy group, carboxyl group, and hydroxyl group observed by H-NMR. Table 1 shows the quantitative results of the carboxyl groups and the average molecular weight of the corresponding samples. Note that GPC was measured in THF solvent, and the number average molecular weight was calculated in terms of polystyrene.
[0050] [Table 1]
[0051] The number of carboxyl groups in ethyl cellulose decreases with increasing molecular weight, suggesting that the carboxyl groups are present at sites that depend on the molecular weight. Since the terminal concentration of polymer decreases with increasing molecular weight of a single molecular chain, it is considered that the quantified carboxyl groups are present at the terminals. In addition, from the perspective of the synthesis reaction scheme of the sample, it can be determined that the carboxyl group analyzed by NMR is present at one terminal.
[0052] Furthermore, assuming that the carboxyl group determined by NMR exists at one end of the ethyl cellulose, the molecular weight of the ethyl cellulose was calculated by determining the number of repeating units of the ethyl cellulose. Table 2 shows the average molecular weights determined by NMR and GPC.
[0053] [Table 2]
[0054] Since the average molecular weight determined by GPC is calculated in terms of polystyrene, the absolute value of the average molecular weight determined by NMR does not match that of the average molecular weight determined by GPC. However, as shown in Figure 4, when comparing the molecular weight values determined by both methods for samples with different molecular weights, a high correlation was observed. This result indicates that a carboxyl group exists at one end of the ethyl cellulose, and it can be said that NMR quantified the carboxyl group present at one end.
[0055] [Preparation of conductive paste] The one-terminal esterified ethyl cellulose (number average molecular weight = 2.0 × 10 4 ) or one-terminated carboxylated ethyl cellulose (number average molecular weight = 2.0 × 10 4 ) at 1.1 parts by mass (2.9 mg / m2 relative to the total surface area of the nickel powder and ceramic powder)2 ) and 39.7 parts by mass of dihydroterpineol acetate as an organic solvent were mixed to obtain a first organic vehicle.
[0056] This first organic vehicle and the BET diameter of 177 nm (SSA (specific surface area) = 3.8 m 2 45.5 parts by mass of nickel powder with a BET diameter of 13 nm (SSA = 77 m 2 3.0 parts by mass of ceramic powder mainly composed of barium titanate (1.0 parts by mass / g) and 0.70 parts by mass of a polycarboxylic acid-based polymer dispersant were mixed and dispersed in a triple roll mill to obtain an intermediate conductive paste.
[0057] Thereafter, the intermediate conductive paste was added with the second binder shown in the "second binder" column of Tables 3 and 4. -One-end esterified ethyl cellulose, Cellulose acetate butyrate, Acrylic binder A (a binder made of polyisobutyl methacrylate), Polyvinyl butyral resins, A mixture of one-terminal esterified ethyl cellulose and polyvinyl butyral resin, A mixture of cellulose acetate butyrate and polyvinyl butyral resin, A mixture of cellulose acetate butyrate and acrylic binder A, Copolymer A (details will be described later), Copolymer B (details will be described later), Copolymer C (details will be described later), Copolymer D (details will be described later), Copolymer E (described in detail below), and Copolymer F (details will be described later), 1.1 parts by mass of any one of the following: Dihydroterpineol acetate 8.9 mass %, A second organic vehicle consisting of the above was added and subjected to a roll dispersion treatment to complete a conductive paste.
[0058] The dispersion method is not limited to the above-mentioned method, and various methods such as a roll mill, a ball mill, a bead mill, high pressure dispersion, etc. This is not limited to the operation for obtaining the conductive paste here, but also applies to other operations.
[0059] Details of each of the copolymers A to F and the experimental procedures for obtaining an organic vehicle (binder solution) containing each of the copolymers A to F are as follows.
[0060] <Copolymer A> Copolymer A is a copolymer of one-terminated ethyl cellulose and acrylic binder B (the main monomer is isobutyl methacrylate, and contains 5 mol % of 2-hydroxyethyl methacrylate).
[0061] Number average molecular weight Mn=2.0×10 4 and 5.5 parts by mass of one-terminal carboxylated ethyl cellulose. 4 The acrylic binder B (5.5 parts by mass) was dried under reduced pressure, and 89 parts by mass of dihydroterpineol acetate was added and dissolved at 50°C under a nitrogen atmosphere. To the resulting solution, 1.5 moles of methacrylic acid (assuming that the total of the Mn-equivalent moles of the one-terminal carboxylated ethyl cellulose and the acrylic binder B is 1 mole), 2.0 moles of diisopropylcarbodiimide as a condensing agent, and 0.01 times the moles of dimethylaminopyridine as a reaction accelerator were added, and the mixture was stirred at a temperature of 50°C for 24 hours to carry out the reaction. This promoted the introduction of methacrylate into the one-terminal carboxylated ethyl cellulose and the acrylic binder B, and the esterification of the hydroxyl groups of the acrylic binder B and the one-terminal carboxylated ethyl cellulose with the carboxyl group of the one-terminal carboxylated ethyl cellulose.
[0062] Next, 0.1 mol (the total of the Mn-equivalent moles of the one-terminal carboxylated ethyl cellulose and the acrylic binder B is taken as 1 mol) of azoisobutyronitrile (AIBN) was mixed as a polymerization initiator for the introduced methacrylate, and the mixture was reacted at 70°C for 5 hours to obtain a binder solution containing copolymer A.
[0063] The obtained copolymer A 1 The formation of ester groups and the disappearance of vinyl groups were confirmed by H-NMR, and the number average molecular weight Mn was 2.3×10 4 As shown above, the number average molecular weight increased from before the reaction, which indicated that the polymerization reaction had progressed. The number average molecular weight was calculated using GPC in THF solvent and converted into polystyrene equivalent.
[0064] <Copolymer B> Copolymer B is a copolymer of one-terminal esterified ethyl cellulose and a polyvinyl butyral resin.
[0065] Number average molecular weight Mn=2.0×10 4 and 5.5 parts by mass of one-terminal esterified ethyl cellulose having a number average molecular weight Mn=2.2×10 4 5.5 parts by mass of polyvinyl acetal resin ("BL-S" manufactured by Sekisui Chemical Co., Ltd.) was dried under reduced pressure, and 89 parts by mass of dihydroterpineol acetate was added and dissolved at 50°C under a nitrogen atmosphere. To the resulting solution, 1.5 moles of methacrylic acid (assuming that the total of the Mn-equivalent moles of the one-terminal esterified ethyl cellulose and the polyvinyl acetal resin is 1 mole), 1.5 moles of diisopropylcarbodiimide as a condensing agent, and 0.01 times the moles of dimethylaminopyridine as a reaction accelerator were added, and the mixture was stirred at a temperature of 50°C for 24 hours to carry out the reaction. This promoted the introduction of methacrylate into the hydroxyl groups of the one-terminal esterified ethyl cellulose and the polyvinyl acetal resin.
[0066] Next, 0.1 mol (the total of the Mn-equivalent moles of the one-end esterified ethyl cellulose and the polyvinyl acetal resin is taken as 1 mol) of azoisobutyronitrile (AIBN) was mixed as a polymerization initiator for the introduced methacrylate, and the reaction was carried out at 70°C for 5 hours to obtain a binder solution containing copolymer B.
[0067] The obtained copolymer B 1 The formation of ester groups and the disappearance of vinyl groups were confirmed by H-NMR, and the number average molecular weight Mn was 2.5×10 4 As shown above, the number average molecular weight increased from before the reaction, which indicated that the polymerization reaction had progressed. The number average molecular weight was calculated using GPC in THF solvent and converted into polystyrene equivalent.
[0068] <Copolymer C> Copolymer C is a copolymer of one-terminated ethyl cellulose and a polyvinyl butyral resin.
[0069] Number average molecular weight Mn=2.0×10 4 and 5.5 parts by mass of one-terminal carboxylated ethyl cellulose having a number average molecular weight Mn=2.2×10 4 5.5 parts by mass of polyvinyl acetal resin ("BL-S" manufactured by Sekisui Chemical Co., Ltd.) was dried under reduced pressure, and 89 parts by mass of dihydroterpineol acetate was added and dissolved at 50°C under a nitrogen atmosphere. To the obtained solution, 1.5 moles of methacrylic acid (assuming that the total of the Mn-equivalent moles of the one-terminal carboxylated ethyl cellulose and the polyvinyl acetal resin is 1 mole), 2.0 moles of diisopropylcarbodiimide as a condensing agent, and 0.01 times the moles of dimethylaminopyridine as a reaction accelerator were added, and the mixture was stirred at a temperature of 50°C for 24 hours to carry out the reaction. This promoted the introduction of methacrylate into the hydroxyl groups of the one-terminal carboxylated ethyl cellulose and the polyvinyl acetal resin, and the esterification of the hydroxyl groups of the polyvinyl acetal resin and the one-terminal carboxylated ethyl cellulose with the carboxyl group of the one-terminal carboxylated ethyl cellulose.
[0070] Next, 0.1 mol (the total of the Mn-equivalent moles of the one-end carboxylated ethyl cellulose and the polyvinyl acetal resin is taken as 1 mol) of azoisobutyronitrile (AIBN) was mixed as a polymerization initiator for the introduced methacrylate, and the mixture was reacted at 70°C for 5 hours to obtain a binder solution containing copolymer C.
[0071] The obtained copolymer C 1 The formation of ester groups and the disappearance of vinyl groups were confirmed by H-NMR, and the number average molecular weight Mn was 2.6×10 4 As shown above, the number average molecular weight increased from before the reaction, which indicated that the polymerization reaction had progressed. The number average molecular weight was calculated using GPC in THF solvent and converted into polystyrene equivalent.
[0072] <Copolymer D> Copolymer D is a copolymer of one-terminated ethyl cellulose and a polyvinyl butyral resin.
[0073] Number average molecular weight Mn=2.0×10 4 and 5.5 parts by mass of one-terminal carboxylated ethyl cellulose having a number average molecular weight Mn=2.2×10 4 5.5 parts by mass of polyvinyl acetal resin ("BL-S" manufactured by Sekisui Chemical Co., Ltd.) was dried under reduced pressure, and 89 parts by mass of dihydroterpineol acetate was added and dissolved at 50°C under a nitrogen atmosphere. 1.1 moles of diisopropylcarbodiimide as a condensing agent (with the Mn-equivalent mole number of one-terminal carboxylated ethyl cellulose as 1 mole) and 0.01 times the mole number of dimethylaminopyridine as a reaction promoter were added to the obtained solution, and the mixture was stirred at a temperature of 50°C for 24 hours to carry out a reaction. As a result, a binder solution containing a copolymer D esterified between a hydroxyl group of the polyvinyl acetal resin and the carboxyl group of the one-terminal carboxylated ethyl cellulose was obtained.
[0074] The obtained copolymer 1The formation of ester groups was confirmed by H-NMR, and the number-average molecular weight Mn was 2.4×10 4 As shown above, the number average molecular weight increased from before the reaction, which indicated that the polymerization reaction had progressed. The number average molecular weight was calculated using GPC in THF solvent and converted into polystyrene equivalent.
[0075] <Copolymer E> Copolymer E is a copolymer of cellulose acetate butyrate and a polyvinyl butyral resin.
[0076] Number average molecular weight Mn=2.0×10 4 5.5 parts by mass of cellulose acetate butyrate ("CAB381-0.1" manufactured by Eastman Co., Ltd.) and a number average molecular weight Mn of 2.2 × 10 4 5.5 parts by mass of polyvinyl acetal resin ("BL-S" manufactured by Sekisui Chemical Co., Ltd.) was dried under reduced pressure, and 89 parts by mass of dihydroterpineol acetate was added and dissolved at 50°C under a nitrogen atmosphere. To the obtained solution, 2 moles of methacrylic acid (the total of the Mn-equivalent moles of cellulose acetate butyrate and polyvinyl acetal resin is 1 mole), 2 moles of diisopropylcarbodiimide as a condensing agent, and 0.01 times the moles of dimethylaminopyridine as a reaction accelerator were added, and the mixture was stirred at a temperature of 50°C for 24 hours to carry out the reaction. This promoted the introduction of methacrylate into cellulose acetate butyrate and polyvinyl acetal resin.
[0077] Next, 0.1 mol (the total number of moles of cellulose acetate butyrate and polyvinyl acetal resin converted into Mn is 1 mol) of azoisobutyronitrile (AIBN) was mixed as a polymerization initiator for the introduced methacrylate, and the reaction was carried out at 70°C for 5 hours to obtain a binder solution containing copolymer E.
[0078] The obtained copolymer 1 The formation of ester groups and the disappearance of vinyl groups were confirmed by H-NMR, and the number average molecular weight Mn was 2.3×10 4As shown above, the number average molecular weight increased from before the reaction, which indicated that the polymerization reaction had progressed. The number average molecular weight was calculated using GPC in THF solvent and converted into polystyrene equivalent.
[0079] <Copolymer F> Copolymer F is a copolymer of cellulose acetate butyrate and acrylic binder B (the main monomer is isobutyl methacrylate, and 5 mol % of 2-hydroxyethyl methacrylate is contained).
[0080] Number average molecular weight Mn=2.0×10 4 5.5 parts by mass of cellulose acetate butyrate ("CAB381-0.1" manufactured by Eastman Co., Ltd.) and a number average molecular weight Mn of 2.1×10 4 The acrylic binder B of 5.5 parts by mass was dried under reduced pressure, and 89 parts by mass of dihydroterpineol acetate was added and dissolved at 50°C under a nitrogen atmosphere. To the obtained solution, 2 moles of methacrylic acid, 2 moles of diisopropylcarbodiimide as a condensing agent, and 0.01 times the moles of dimethylaminopyridine as a reaction accelerator were added (the total of the Mn-equivalent moles of cellulose acetate butyrate and polyvinyl acetal resin was 1 mole), and the mixture was stirred at a temperature of 50°C for 24 hours to carry out the reaction. This promoted the introduction of methacrylate into cellulose acetate butyrate and acrylic binder B.
[0081] Next, 0.1 moles (the total number of moles of cellulose acetate butyrate and polyvinyl acetal resin converted into Mn is taken as 1 mole) of azoisobutyronitrile (AIBN) was mixed as a polymerization initiator for the introduced methacrylate, and the reaction was carried out at 70°C for 5 hours to obtain a binder solution containing copolymer F.
[0082] The obtained copolymer 1 The formation of ester groups and the disappearance of vinyl groups were confirmed by H-NMR, and the number average molecular weight Mn was 2.4×10 4As shown above, the number average molecular weight increased from before the reaction, which indicated that the polymerization reaction had progressed. The number average molecular weight was calculated using GPC in THF solvent and converted into polystyrene equivalent.
[0083] [Evaluation of binder adsorption amount of conductive paste] The amount of binder adsorption of the prepared conductive paste was evaluated by the following procedure.
[0084] 400cc of acetone was added to 200cc of conductive paste, and the mixture was stirred for 30 minutes with a planetary mixer. The mixture was then centrifuged for 15 minutes at 29000 rpm with a himac CS100FNX to precipitate the nickel powder and ceramic powder, and the supernatant was separated. The separated supernatant contained unadsorbed binder, so the organic solids concentration in the total supernatant was calculated from the weight change when dried. The total organic solids content in the conductive paste was calculated from the weight change when the dried paste was heated to 1000°C with a TG-DTA (thermogravimetric differential thermal analyzer) in a N2 atmosphere.
[0085] The amount of binder adsorption relative to the total surface area of the nickel powder and ceramic powder was calculated by applying the values obtained above to the following formula.
[0086] Binder adsorption amount = (total organic solids amount - total organic solids amount in supernatant - total amount of dispersant charged) / total surface area of nickel powder and ceramic powder In addition, since the conductive paste used as the sample used a polycarboxylic acid-based dispersant, the adsorption state was essentially irreversible, and calculations were performed assuming that the supernatant did not contain any dispersant.
[0087] The determined binder adsorption amounts are shown in Tables 3 and 4 in the column "Binder adsorption amount relative to the total surface area of nickel powder and ceramic powder."
[0088] [Evaluation of binder adsorption amount and adsorbed matter of conductive paste] For Comparative Example 1-1 and Example 1-1, the following evaluations (1) and (2) were additionally performed to evaluate the amount of adsorption of the binder and the adsorbed substances.
[0089] <Evaluation (1)> 400cc of acetone was added to 200cc of conductive paste, and after stirring for 30 minutes with a planetary mixer, it was centrifuged for 15 minutes at 33,000 rpm with a himac "CS100FNX" to precipitate the nickel powder and ceramic powder, and the supernatant was separated. The separated supernatant was dried, and the resulting dried solids (i.e., unadsorbed binder) were converted to TMS and subjected to NMR measurement to identify the unadsorbed binder. If the supernatant contained multiple types of binders or dispersants, it was necessary to separate it using HPLC (high performance liquid chromatography).
[0090] <Evaluation (2)> 400 cc of acetone was added to the solids precipitated by the centrifugation in Evaluation (1), and the mixture was stirred for 30 minutes at 12,000 rpm using a homogenizer "MARK II" manufactured by Primix Corporation, thereby desorbing a portion of the binder adsorbed on the particle surfaces.
[0091] Next, the mixture was centrifuged at 29,000 rpm for 15 minutes using a centrifuge (himac's "CS100FNX") to precipitate the nickel powder and ceramic powder, and the supernatant was separated. The separated supernatant was dried, and the resulting dried solid supernatant was converted to TMS and subjected to NMR measurement to identify the adsorbed binder. Note that when multiple types of binders or dispersants are included, separation by HPLC is required.
[0092] As a result, in Comparative Example 1-1, one-terminal esterified ethyl cellulose was detected in both evaluation (1) and evaluation (2), while in Example 1-1, one-terminal esterified ethyl cellulose and one-terminal carboxylated ethyl cellulose were detected in evaluation (1) at a ratio of (one-terminal esterified ethyl cellulose):(one-terminal carboxylated ethyl cellulose)=about 3:1, and in evaluation (2), one-terminal esterified ethyl cellulose and one-terminal carboxylated ethyl cellulose were detected in a ratio of (one-terminal esterified ethyl cellulose):(one-terminal carboxylated ethyl cellulose)=about 1:7. From this, it was determined that a paste in which one-terminal carboxylated ethyl cellulose was adsorbed on the surfaces of the nickel particles and the ceramic particles could be prepared.
[0093] [Preparation of unfired laminated chips] A ceramic material composed mainly of barium titanate with a BET diameter of 150 nm, a polyvinyl butyral resin, a solvent of toluene and echinacene in a ratio of 5:5, and a plasticizer, triethylene glycol di(2-ethylhexanoate), were mixed in a specified ratio and subjected to a wet dispersion process using a bead mill to obtain a ceramic slurry.
[0094] Next, this ceramic slurry was formed on a PET (polyethylene terephthalate) film using a doctor blade method so as to have a thickness of 1.0 μm after drying, thereby obtaining a ceramic green sheet.
[0095] Next, the conductive paste for the above-mentioned sample was printed on the ceramic green sheet using a screen printer in a pattern such that the planar dimensions of the resulting cut and fired chip-shaped laminate would be 1.0 mm x 0.5 mm, and the nickel thickness after drying would be an average of 0.30 μm (measured by X-ray fluorescence analysis (XRF)) and the physical thickness would be an average of 0.60 μm (observed by focused ion beam (FIB) processed cross-section scanning electron microscope (SEM)), to form a conductive paste coating to serve as the internal electrodes.
[0096] Next, after peeling each ceramic green sheet from the PET film, first, 50 ceramic green sheets not printed with a conductive paste coating were stacked, then 350 ceramic green sheets printed with a conductive paste coating were stacked, and then 30 ceramic green sheets not printed with a conductive paste coating were stacked to obtain a laminated structure, which was then placed in a predetermined mold. Next, the laminated structure in the mold was pressed to obtain an unfired laminate. The obtained unfired laminate was heated to 90°C and cut to a predetermined size by pressing to obtain an unfired laminate chip.
[0097] [Evaluation of structural defects] For each of 100 unsintered laminate chips randomly selected from the above unsintered laminate chips, the cut surface of the pressed chip was observed using an optical microscope to confirm the presence or absence of cohesive failure in the conductive coating film (peeling within the internal electrode layer) as a structural defect.
[0098] The number of laminate chips in which structural defects were observed among 100 laminate chips is shown in the "Structural Defects" column in Tables 3 and 4. In addition, based on the number of laminate chips in which structural defects were observed, the occurrence of structural defects was evaluated according to the following criteria. ⊚: The number of laminates in which structural defects were observed was 0 or 1. ◯: The number of laminates in which structural defects were observed was 2 or more and 5 or less. ×: Structural defects were observed in 6 or more laminates.
[0099] [Table 3]
[0100] [Table 4]
[0101] A comparison of Comparative Examples 1-1 to 1-13 shown in Table 3 with Examples 1-1 to 1-13 shown in Table 4 shows that by adsorbing one-end-carboxylated ethyl cellulose as the first binder onto nickel particles and ceramic particles, the number of structural defects can be significantly reduced without any particular selection of the type of binder added as the second binder.
[0102] Polymeric comb-type dispersants such as polycarboxylic acid-based dispersants and low-molecular-weight one-end adsorbing dispersants arrange their molecular chains at narrow intervals on the surface of inorganic particles to form steric repulsion sites, which creates the problem that adhesive strength between the binder and the dispersant molecular chains is difficult to manifest (poor compatibility) due to steric constraints. In contrast, when high-molecular-weight one-end carboxylated ethyl cellulose is adsorbed at one end to the surface of inorganic particles, the molecular chains are arranged at wide intervals, making it difficult for steric constraints to arise and it is thought that adhesive strength between the binder and one-end carboxylated ethyl cellulose is easily manifested (good compatibility).
[0103] In addition, from a comparison between Examples 1-5 to 1-7 and Examples 1-8 to 1-13, it can be seen that using a copolymer having a cellulose derivative portion as a binder as in Examples 1-8 to 1-13 is more effective in suppressing structural defects than using a mixture of cellulose derivatives as in Examples 1-5 to 1-7. This is presumably because the adhesiveness of the interface between the different binders in the mixed binder systems as in Examples 1-5 to 1-7 is weak, and cohesive failure (peeling within the internal electrode layer) occurs from there.
[0104] In addition, a comparison of Examples 1-1 to 1-2 with Examples 1-8 to 1-13 shows that a copolymer of a cellulose derivative having a high Tg (glass transition point) and a different binder having a low Tg is softer and less susceptible to breakage than a composition consisting of only a cellulose derivative having a high Tg.
[0105] Experimental Example 2 In Experimental Example 2, the binder adsorption amount and the occurrence of structural defects were evaluated in the same manner as in Experimental Example 1 for samples in which the composition of the organic vehicle in the conductive paste was changed.
[0106] [Preparation of conductive paste] In order to obtain Examples 2-1 to 2-4 shown in Table 5, a BET diameter of 177 nm (SSA=3.8 nm) was used. 2 45.5 parts by mass of nickel powder with a BET diameter of 13 nm (SSA = 77 m 2 3.0 parts by mass of ceramic powder mainly composed of barium titanate (1.0 parts by mass / g), 0.70 parts by mass of a polycarboxylic acid-based polymer dispersant, and 2.0×10 4 The one-terminal carboxylated ethyl cellulose was mixed in the amount shown in the "First Binder" column of Table 5 with 39.7 parts by mass of dihydroterpineol acetate as an organic solvent, and the mixture was subjected to a roll dispersion process to obtain an intermediate conductive paste.
[0107] Then, the aforementioned copolymer C as a second binder in the mass part shown in the "Second Binder" column in Table 5 and 8.9 mass parts of dihydroterpineol acetate were added to this intermediate conductive paste, and the mixture was dispersed using a three-roll mill to obtain the conductive pastes of Examples 2-1 to 2-4 shown in Table 5.
[0108] On the other hand, in order to obtain Example 2-5 shown in Table 5, the BET diameter was set to 177 nm (SSA=3.8 m 2 45.5 parts by mass of nickel powder with a BET diameter of 13 nm (SSA = 77 m 2 3.0 parts by mass of ceramic powder mainly composed of barium titanate (1.0 parts by mass / g), 0.70 parts by mass of a polycarboxylic acid-based polymer dispersant, and 2.0×10 4 1.6 parts by mass of the one-terminal carboxylated ethyl cellulose and 39.2 parts by mass of dihydroterpineol acetate were mixed and subjected to a roll dispersion treatment to obtain an intermediate conductive paste.
[0109] Then, the intermediate conductive paste was mixed with a second binder having a number average molecular weight of 2.0×10 41.1 parts by mass of one-terminal carboxylated ethyl cellulose and 8.9 parts by mass of dihydroterpineol acetate were added, and dispersed using a three-roll mill to obtain a conductive paste according to Example 2-5 shown in Table 5.
[0110] [Table 5]
[0111] [Evaluation of binder adsorption amount and occurrence of structural defects] The amount of binder adsorption relative to the total surface area of the nickel powder and the ceramic powder, and the number of structural defects when the unfired laminate was pressed and cut were evaluated in the same manner as in Experimental Example 1. The results are shown in Table 6.
[0112] [Table 6]
[0113] From Table 6, the adsorption amount of one-terminated carboxylated ethyl cellulose relative to the total surface area of nickel powder and ceramic powder is 1.0 mg / m 2 ≥ 5.0 mg / m 2 The following proves to be particularly suitable:
[0114] Experimental Example 3 In Experimental Example 3, samples in which the molecular weight of the cellulose derivative contained in the conductive paste was different were prepared in the same manner as in Experimental Example 1.
[0115] [Preparation of conductive paste] BET diameter 177nm (SSA=3.8m 2 45.5 parts by mass of nickel powder with a BET diameter of 13 nm (SSA = 77 m 23.0 parts by mass of ceramic powder mainly composed of barium titanate (wt. / g), 0.70 parts by mass of a polycarboxylic acid-based polymer dispersant, 1.1 parts by mass of one-terminal carboxylated ethyl cellulose having a number average molecular weight shown in the "First Binder" column of Table 7 as a first binder, and 39.7 parts by mass of dihydroterpineol acetate were mixed and subjected to a roll dispersion process to obtain an intermediate conductive paste.
[0116] Then, 1.1 parts by mass of the aforementioned copolymer C as a second binder and 8.9 parts by mass of dihydroterpineol acetate were added to the intermediate conductive paste, and the mixture was dispersed using a three-roll mill to obtain the conductive pastes of Examples 3-1 to 3-3 shown in Table 7.
[0117] [Evaluation of binder adsorption amount and occurrence of structural defects] The binder adsorption amount relative to the total surface area of the nickel powder and the ceramic powder and the number of structural defects when the unsintered laminate was pressed and cut were evaluated in the same manner as in Experimental Example 1. The results are shown in Table 7. Table 7 also shows the evaluation results of Examples 1-10 produced in Experimental Example 1.
[0118] [Table 7]
[0119] From Table 7, even if the molecular weight of the one-terminal carboxylated ethyl cellulose adsorbed on the nickel particles and the ceramic particles was changed, the amount of adsorption did not change significantly, and no structural defects were observed. From this, it can be seen that there is no particular restriction on the molecular weight of the one-terminal carboxylated ethyl cellulose in order to obtain the effects of this invention.
[0120] The reason why there was no significant change in the amount of adsorption even when the molecular weight was changed is presumably due to a balanced relationship in which, as the molecular chains of the single-end-carboxylated ethyl cellulose become shorter, the repulsion between the molecular chains adsorbed on the surfaces of the nickel particles and ceramic particles becomes smaller, and the number of adsorbed strands of single-end-carboxylated ethyl cellulose increases, whereas, as the molecular chains of the single-end-carboxylated ethyl cellulose become longer, the repulsion between the molecular chains adsorbed on the surfaces of the nickel particles and ceramic particles becomes greater, and the number of adsorbed strands of single-end-carboxylated ethyl cellulose decreases.
[0121] Experimental Example 4 In Experimental Example 4, samples were prepared using the same method as in Experimental Example 1, in which the paste contained different types of inorganic particles.
[0122] [Preparation of conductive paste] BET diameter 204nm (SSA=3.4m 2 45.5 parts by mass of decanoic acid-coated Cu powder with a BET diameter of 13 nm (SSA = 77 nm) 2 3.0 parts by mass of ceramic powder mainly composed of barium titanate (1.0 parts by mass / g), 0.35 parts by mass of a polycarboxylic acid-based polymer dispersant, and 2.0×10 4 0.8 parts by mass of the one-terminal carboxylated ethyl cellulose and 40.05 parts by mass of dihydroterpineol acetate were mixed and subjected to a roll dispersion treatment to obtain an intermediate conductive paste.
[0123] Then, 1.4 parts by mass of the aforementioned copolymer C as a second binder and 8.9 parts by mass of dihydroterpineol acetate were added to the intermediate conductive paste, and the mixture was dispersed using a three-roll mill to obtain the conductive paste of Example 4-1 shown in Table 8.
[0124] [Preparation of ceramic paste] BET diameter 149 nm (SSA = 6.7 m 233.6 parts by mass of a powder mainly composed of barium titanate (1.0 parts by mass / g), 0.45 parts by mass of a polycarboxylic acid-based polymer dispersant, and a 2.0×10 4 0.4 parts by mass of the one-terminal carboxylated ethyl cellulose and 40.05 parts by mass of dihydroterpineol acetate were mixed and subjected to a roll dispersion treatment to obtain an intermediate ceramic paste.
[0125] Then, 3.0 parts by mass of the aforementioned copolymer C as a second binder and 22.5 parts by mass of dihydroterpineol acetate were added to the intermediate ceramic paste, and the mixture was dispersed using a three-roll mill to obtain the ceramic paste of Example 4-2 shown in Table 8.
[0126] [Preparation of unfired laminated chips] For the conductive paste according to Example 4-1, a green laminate chip was obtained in the same manner as in Experimental Example 1.
[0127] For the ceramic paste of Example 4-2, an unfired laminate chip was obtained by the method described below.
[0128] A ceramic material composed mainly of barium titanate with a BET diameter of 150 nm, a polyvinyl butyral resin, a solvent of toluene and echinacene in a ratio of 5:5, and a plasticizer, triethylene glycol di(2-ethylhexanoate), were mixed in a specified ratio and subjected to a wet dispersion process using a bead mill to obtain a ceramic slurry.
[0129] Next, this ceramic slurry was formed on a PET (polyethylene terephthalate) film using a doctor blade method so as to have a thickness of 1.0 μm after drying, thereby obtaining a ceramic green sheet.
[0130] Next, the conductive paste according to the above-mentioned Example 1-10 was printed on the ceramic green sheet by a screen printer in a pattern such that the planar dimensions of the chip-shaped laminate obtained later after cutting and firing would be 1.0 mm × 0.5 mm, and the nickel thickness after drying would be 0.30 μm (XRF measurement) and the average physical thickness would be 0.60 μm (FIB-processed cross-sectional SEM observation) to form a conductive paste coating to serve as an internal electrode.
[0131] Thereafter, in the areas where no conductive paste coating was formed, the ceramic paste of Example 4-2 shown in Table 8 was printed using a screen printer to have an average physical thickness of 0.30 μm (FIB processed cross-section SEM observation), thereby forming a coating to compensate for the step caused by the thickness of the conductive paste coating that was to become the internal electrode.
[0132] Next, after peeling off each ceramic green sheet from the PET film, first, 50 ceramic green sheets not printed with a conductive paste coating were stacked, then 350 ceramic green sheets printed with a conductive paste coating were stacked, and 30 ceramic green sheets not printed with a conductive paste coating were stacked to obtain a laminated structure, which was then placed in a predetermined mold. Next, the laminated structure in the mold was pressed to obtain an unfired laminate. The obtained unfired laminate was heated to 90°C and cut to a predetermined size by pressing to obtain an unfired laminate chip according to Example 4-2.
[0133] [Evaluation of structural defects] For Example 4-1, the binder adsorption amount relative to the total surface area of the nickel powder and the ceramic powder and the number of structural defects when the unsintered laminate was cut were evaluated in the same manner as in Example 1.
[0134] On the other hand, for Example 4-2, 100 unsintered laminate chips were randomly selected from the above-mentioned unsintered laminate chips, and the cut surfaces of each were observed using an optical microscope to confirm the presence or absence of cohesive failure in the conductive paste coating or the step compensation coating as a structural defect (peeling within the internal electrode layer or the step compensation coating).
[0135] The number of stack chips in which structural defects were observed among 100 stack chips is shown in the "Structural Defects" column in Table 8. The "Judgment" in Table 8 follows the same criteria as the "Judgment" in Tables 3 and 4.
[0136] [Table 8]
[0137] From Table 8, it can be seen that if the binder was confirmed to have an adsorption effect when combined with nickel particles, the same effect can be obtained when combined with other metal particles such as copper particles, or with ceramic particles such as BaTiO3 particles. This shows that the inorganic particles contained in the paste for electronic components can be any inorganic particles as long as they are inorganic particles capable of adsorbing a cellulose derivative having a carboxyl group at one end or a carboxylate at one end. [Explanation of symbols]
[0138] 1 Inorganic particles 2. Comb-type polymer dispersants 3. Low molecular weight dispersants 4. Second Binder 5. First Binder
Claims
1. The composition includes inorganic particles, a dispersant, a binder, and an organic solvent, the binder includes a first binder adsorbed on the surface of the inorganic particle and a second binder not adsorbed on the surface of the inorganic particle, At least the first binder is a cellulose derivative having a terminal carboxyl group or a terminal carboxylate group; Paste for electronic components.
2. 2. The paste for electronic components according to claim 1, wherein the second binder is a cellulose derivative having a carboxyl group at one end or a carboxylate at one end.
3. 2. The paste for electronic components according to claim 1, wherein the second binder is a cellulose derivative having no terminal carboxyl group or no terminal carboxylate.
4. The paste for electronic components according to claim 1 , wherein the second binder is a copolymer having a cellulose derivative portion or a mixture of multiple polymers containing a cellulose derivative.
5. The cellulose derivative having a carboxyl group at one end or a carboxylate at one end as the first binder is in an amount of 1.0 mg / m with respect to the total surface area of the inorganic particles. 2 or more and 5.0 mg / m 2 The paste for electronic parts according to any one of claims 1 to 4, comprising:
6. 5. The paste for electronic components according to claim 1, wherein the inorganic particles include at least one of ceramic particles and metal particles.
7. 7. The paste for electronic components according to claim 6, wherein the ceramic particles contain at least one element selected from the group consisting of Ba, Ti, Ca, Zr and Sr.
8. The paste for electronic components according to claim 6 , wherein the metal particles contain at least one metal selected from the group consisting of Cu, Ni, Au and Ag.
9. 5. A paste for electronic parts according to claim 1, wherein the cellulose derivative having a carboxyl group at one end or a carboxylate at one end is a cellulose ether having a carboxyl group at one end or a carboxylate at one end.
10. 10. The paste for electronic components according to claim 9, wherein the cellulose ether having a carboxyl group at one end or a carboxylate salt at one end is at least one selected from the group consisting of methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, ethyl hydroxyethyl cellulose and hydroxypropyl methyl cellulose.
11. 5. The paste for electronic parts according to claim 1, wherein the dispersant is a polymer dispersant.
12. The paste for electronic components according to claim 11, wherein the polymer dispersant is a polycarboxylic acid-based dispersant.
Citation Information
Patent Citations
Nickel paste and method for producing the same, and nickel organic slurry and method for producing the same
JP2018131681A
Conductive paste
JP2018168238A
Conductive paste and method for producing electronic component using the same
JP2021051916A